Public Private Partnership in Non-Metro Airports Model Concession Agreement - Planning Commission (Planning Commission, 2010)
Civil aviation has been one of the fastest growing among all the infrastructure sectors in India. It has transformed from a means of transport for the elite to one which is effectively competing with rail and road transport. During the Eleventh Plan, passenger and cargo traffic are expected to increase by about 19 per cent per and 11 per cent annum respectively. By 2020, Indian airports are expected to handle more than 100 million passengers, including 60 million domestic passengers, and about 3.4 million tonnes of cargo per annum.
Planning Commission Government Of India
Planning Commission Government of India